Experimental study on thermal performance of optimum PG brine as a radiator coolant - Sahoo R.R. (My University, 2025)
The present study deals with the experimental impact of an alternative heat transfer fluids for overall performance improvement for radiators. Water and water mixed with anti-freezing agents such as ethylene glycol (EG) and propylene glycol (PG) are the traditional coolants for an automotive radiator. Comparison of experimental and numerical analysis of optimum brine solution, that is 25% of propylene glycol and water as coolant for the rectangular fin radiator, has been well discussed. A closed loop test rig was designed, and fabricated with a wind tunnel section to achieve uniform velocity at the test section of the rectangular radiator and was tested for performance. Experimental runs were conducted at varying operating temperatures which included the runs for water, and an optimum propylene glycol brine solutions at 70 °C and 80 °C with various flow rates. Results show the energy performance of an optimum brine solution was nearly similar to that of water at high temperatures. The Nusselt number, heat transfer coefficient, and heat transfer rate for an optimum propylene glycol brine is nearly the same as water at 80 °C with a maximum deviation of 15%, 5.7%, and 6.6%, respectively, for theoretical and experimental result comparisons. Air side and coolant side pressure drops had a maximum deviation of 3.66% and 6.6%, respectively. Air and coolant exit temperatures had a deviation of 5% and 3.5%, respectively, with an air frontal velocity of 4.6 m/s in a rectangular fin radiator for an optimum brine solution used as coolant for the automotive radiator. The optimum propylene glycol brine may be environmentally beneficial. © 2017 Wiley Periodicals, Inc.